2023
DOI: 10.3390/vetsci10070481
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Whole Genome Analysis of Chicken Infectious Anemia Virus in an Outbreak of Disease in Adult Layer Hens

Yueyan Zeng,
Hui Zhang,
Huanrong Zhang

Abstract: Chicken infectious anemia (CIA) poses a significant threat to the chicken industry in China. Due to its non-specific symptoms, the disease is often overlooked. This study aimed to conduct a comprehensive analysis of the etiology and pathology of CIA in Guangxi Province, China. Three strains of the chicken infectious anemia virus (CIAV) were isolated from liver samples of diseased 20-week-old chickens. The complete genomes of these strains were sequenced, and experiments on specific pathogen-free (SPF) chicks r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Owing to its nonspecific symptoms, this disease is frequently overlooked. Nonetheless, it is noteworthy that outbreaks of CIAV infection have been documented in 20-week-old laying hens, especially in instances of co-infection where immunosuppressive factors could be significant [12]. In vitro infection and proliferation experiments revealed that CIAV replicated in chicken embryos and lymphoblastic cell lines, but not in chicken embryo fibroblasts (CEFs), chicken kidney cells, or other primary cell types [13].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its nonspecific symptoms, this disease is frequently overlooked. Nonetheless, it is noteworthy that outbreaks of CIAV infection have been documented in 20-week-old laying hens, especially in instances of co-infection where immunosuppressive factors could be significant [12]. In vitro infection and proliferation experiments revealed that CIAV replicated in chicken embryos and lymphoblastic cell lines, but not in chicken embryo fibroblasts (CEFs), chicken kidney cells, or other primary cell types [13].…”
Section: Introductionmentioning
confidence: 99%